2020
DOI: 10.1093/cid/ciaa386
|View full text |Cite
|
Sign up to set email alerts
|

New Measures for the Coronavirus Disease 2019 Response: A Lesson From the Wenzhou Experience

Abstract: As the outbreak of coronavirus disease 2019 (COVID-19) has spread globally, determining how to prevent the spread is of paramount importance. We reported the effectiveness of different responses of 4 affected cities in preventing the COVID-19 spread. We expect the Wenzhou anti–COVID-19 measures may provide information for cities around the world that are experiencing this epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 7 publications
2
35
0
1
Order By: Relevance
“…Retrospective analyses of NPI impact on disease spread, to date, have primarily consisted of cross-country analyses or focused on outcomes in China. 2,20,21,[23][24][25] In one comparison of 20 countries, Banholzer et al found public venue closures to be the most effective NPI in reducing new cases, followed by public gathering bans, non-essential business closures, and international travel restrictions, with school closures decreasing case count minimally. Interestingly, they found 'lockdowns' to be among the least effective policies in mitigating disease spread.…”
Section: Context and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective analyses of NPI impact on disease spread, to date, have primarily consisted of cross-country analyses or focused on outcomes in China. 2,20,21,[23][24][25] In one comparison of 20 countries, Banholzer et al found public venue closures to be the most effective NPI in reducing new cases, followed by public gathering bans, non-essential business closures, and international travel restrictions, with school closures decreasing case count minimally. Interestingly, they found 'lockdowns' to be among the least effective policies in mitigating disease spread.…”
Section: Context and Contributionmentioning
confidence: 99%
“…2 Analysis at the city level in China has also associated comprehensive social distancing measures with preventing disease spread. 23,24 In Wuhan, a reduction in Rt was shown to chronologically follow implementation of traffic restrictions, home confinement, centralized quarantine, and other social distancing measures. 23 The United States presents unique challenges in epidemiological management due to its governmental emphasis on state and local autonomy.…”
Section: Context and Contributionmentioning
confidence: 99%
“…Although these countries have successfully reduced case numbers, no causal relationship between use of app technology and epidemic control has yet been shown. 9 , 10 , 11 , 12 , 13 , 14 Many uncertainties remain on the optimal process of contact tracing with conventional methods or mobile apps, on the timing of testing for current or past infection, and on the required coverage of contact tracing needed.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Duration of the SARS-CoV-2 viral loading: The virus load was fluctuated largely around the average level throughout the entire epidemic period [ 30 , 31 ] without a clear peak ( Figure 4A ). This indicated that the virus load was probably not a contributing factor to the dynamic of epidemic.…”
Section: Resultsmentioning
confidence: 99%
“…The patients were consecutively enrolled from 23 January to 3 March 2020 [ 30 , 31 ] in six medical centers and CDCs in Zhejiang province, China, including site 1 (Affiliated Taizhou Hospital of WMU), Site 2 (Wenzhou municipal CDC, WZ CDC), Site 3 (Zhejiang provincial CDC, ZJ CDC), Site 4 (1st affiliated hospital of WMU), Site 5 (2nd affiliated hospital of WMU) and Site 6 (Affiliated eye hospital of WMU). A total of 252 confirmed COVID-19, 54 COVID-19 convalescent and 300 COVID-19 negative, cases were included in the study cohort (see Table 2 ).…”
Section: Methodsmentioning
confidence: 99%